Philippines : Financial Sector Assessment Program-Technical Note on Macroprudential Policy Framework and Tools. (IMF Staff Country Reports; Country Report ;, 2022)
The Bangko Sentral Ng Pilipinas (BSP), together with the other financial sector regulators and the Department of Finance (DoF), made significant progress in developing a framework for macroprudential supervision. The BSP plays a central role as the bank and payment system supervisor, as well as macroprudential authority with with its financial stability mandate obtained in 2019, and the chair of inter-agency coordination mechanisms (Financial Stability Coordination Council, FSCC). The FSCC was established in 2011 as a voluntary interagency body (without decision-making powers) to coordinate macroprudential policies and crisis management and include the BSP, Securities Exchange Commission (SEC), Insurance Commission (IC), Philippine Deposit Insurance Commission (PDIC) and the DoF. Within the BSP, a financial stability "unit" (OSRM, established in 2017) works on macroprudential analysis and policy preparation. BSP's Financial Stability Policy Committee (FSPC), a Monetary Board (MB) subcommittee established in 2020, decides on macroprudential issues, while policy decision making on monetary policy and financial sector supervision takes place in the MB.